Clinical efficacy of the radius bone plates for the fixation of radius bone fractures - Kumar, Tarun; Beriwal, Mridul; Chawale, Bhawana; Kumar, Mohit; Luthra, Gaurav (International Journal of Research in Orthopaedics, 2022)
Background: The purpose of this study was to evaluate the clinical efficacy of the radius bone plates fixation for treating radius bone fracture. Methods: Forty-Five patients with fracture of the radius involving the distal part were treated with fixed angle plate fixation approach. This was a retrospective study in which 45 patients (39M, 6F) were treated at different hospitals and countries between August 2020 to October 2021 with a mean follow up of year (1month, 3months, 6months and 12months). All patients were followed using radiographs, physical examination, ASA and VAS score. Results: All patients with radius fracture treated with specific fixation of plate system were enrolled and received continuous physiotherapy by physiotherapists, which helped in early healing. The clinical treatment results showed decline in the VAS score percentage after 1 year follow up. About 91.1% patients were satisfied with no pain and 8.8% patients were unsatisfied due to mild pain. A successful surgical outcome was reported without any complications related to implant breakage, loosening, corrosion or other factors. Conclusions: The radius plate system results in more efficient, stable fixation and better subjective results early in the postoperative period. It has minimal complications requiring reoperation and risks.